2001
DOI: 10.1097/00007890-200101150-00008
|View full text |Cite
|
Sign up to set email alerts
|

Successful Outcome With a ???Quintuple Approach??? Of Posttransplant Lymphoproliferative Disorder

Abstract: This combined approach resulted in a favorable outcome in patients with high risk monoclonal PTLD after solid organ transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 26 publications
0
23
0
1
Order By: Relevance
“…Based on the correlation in humans and the experimental data in SCID mice, high-dose i.v. gamma globulin, containing high levels of anti-EBV Abs, has been incorporated into some combined treatment protocols for posttransplant lymphoproliferative disorders following solid organ transplant (48,50). However, Ig therapy is not widely used in the prevention and treatment of posttransplant lymphoproliferative syndromes, and only recently have clinical trials been initiated to establish the efficacy of anti-viral Ab therapy (48).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the correlation in humans and the experimental data in SCID mice, high-dose i.v. gamma globulin, containing high levels of anti-EBV Abs, has been incorporated into some combined treatment protocols for posttransplant lymphoproliferative disorders following solid organ transplant (48,50). However, Ig therapy is not widely used in the prevention and treatment of posttransplant lymphoproliferative syndromes, and only recently have clinical trials been initiated to establish the efficacy of anti-viral Ab therapy (48).…”
Section: Discussionmentioning
confidence: 99%
“…IgG therapy (53)(54)(55)(56). Especially in the case of neurotropic viruses, Abs have been shown to limit or prevent virus spread to the CNS system or restrict virus expression (57)(58)(59)(60).…”
Section: Different Strategies Leading To Similar Outcomes: Mmtv Vs Ebvmentioning
confidence: 99%
“…4 There is ample evidence that an adoptive immunotherapy approach with transfer of lymphocytes or EBV-specific CTLs of donor origin is effective as prophylaxis and/or treatment of EBV-related PTLD in recipients of T-cell-depleted BMT [5][6][7][8] ; data have shown that anti-CD20 monoclonal antibody can be an equally useful therapeutic strategy when donor-derived EBV CTLs are not available. 9,10 Conversely, treatment of PTLD in patients receiving organ allografts who fail to respond to reduction or discontinuation of immunosuppression, [11][12][13] is still controversial. Antiviral drugs, 12 ␣ interferon, [12][13][14] anti-Bcell monoclonal antibodies, 12,15 and chemotherapy 13,16,17 have all been used and reported to induce remission in selected cases, and, as described for BMT recipients, also in the setting of SOT the use of anti-CD20 has proved effective in resolving established PTLD.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Conversely, treatment of PTLD in patients receiving organ allografts who fail to respond to reduction or discontinuation of immunosuppression, [11][12][13] is still controversial. Antiviral drugs, 12 ␣ interferon, [12][13][14] anti-Bcell monoclonal antibodies, 12,15 and chemotherapy 13,16,17 have all been used and reported to induce remission in selected cases, and, as described for BMT recipients, also in the setting of SOT the use of anti-CD20 has proved effective in resolving established PTLD. 18 Notwithstanding the 50% to 85% remission rate attained by the reported therapeutic approaches, frequent complications such as rejection, toxicity, and other infectious pathologies heavily compromise graft and host survival; moreover, overall mortality in patients with unresponsive PTLD remains high.…”
Section: Introductionmentioning
confidence: 99%